Honeycomb-lattice antiferromagnet Mn2V2O7: a temperature-dependent x-ray diffraction, neutron diffraction and ESR study. (3rd April 2017) - Sun, Y C; Ouyang, Z W; Xiao, Y; Su, Y; Feng, E; Fu, Z; Jin, W T; Zbiri, M; Xia, Z C; Wang, J F; Rao, G H
Abstract: Temperature-dependent x-ray diffraction (XRD), neutron powder diffraction and high-field electron spin resonance (ESR) have been employed to study the structural and magnetic properties of distorted honeycomb lattice Mn2 V2 O7 . The XRD data reveal that upon cooling Mn2 V2 O7 undergoes a martensitic-like β – α structural phase transition at 270 K. Upon heating, however, the reversible α–β structural transition takes place at 210 K, showing the first-order feature of the transition. The temperature range, where the two phases coexist, is well determined. With further decrease in temperature, a paramagnetic-to-antiferromagnetic (AFM) phase transition takes place at T N = 23 K as indicated by ESR and neutron powder diffraction data. The ESR data demonstrate the AFM resonance modes below T N, which can be well understood by conventional AFM resonance theory with uniaxial anisotropy.